Prevalence and Risk Factors of Internet Gaming Disorder Under the COVID-19 Pandemic Among University Students in Macao - Yan Wang PhD; Ming Liu PhD; Oi Ching Bernice Lam Nogueira PhD (SAGE Publishing, 2023)
Introduction During the COVID-19 pandemic, the zero-tolerance policy implemented in Macao affected university students' life and learning styles. Objectives This study aimed to investigate the prevalence of internet gaming disorder (IGD) and analyze its risk factors among university students of Macao amid the COVID-19 pandemic. Methods Two hundred and twenty-nine university students were recruited by convenience sampling. The cross-sectional investigation was conducted using the 9-item Chinese version of the IGD Scale, the Chinese Version of the Self-Compassion Scale, and the Chinese version of the Brief Resilience Scale. Results The prevalence was 7.4%. Compared to Non-IGD gamers, the IGD gamers were more likely to be the older, male gender, with a longer gaming history, with more game hours per day in the last month, and with a lower self-compassion score and resilience. Conclusion The prevalence of IGD increased. Students who are the older, male gender, with more gaming time, low self-compassion, and low resilience, have a high possibility of IGD.